Comparison of Pulmonary Functions in Petrol Pump Workers and Residents of Oil Refinery - Satyanath Reddy Kodidala; Ali Mohamad Ahanger; Asha Gandhi (Indian Journal of Medical Specialities)
Background: Health of human beings depends on their environment. Petrol pump workers (PPWs) are exposed to petrol/diesel fumes containing toxic compounds, which may affect the capability of lungs. Similarly, residents living around the oil refinery are exposed to pollutants, which may have deleterious effects on pulmonary health. Objectives: The study aimed to assess pulmonary function tests (PFTs) in residents living near an oil refinery and PPWs and compared with the control group. Materials and Methods: The study group (age: 20–45 years) comprised PPWs in Mathura district generally exposed to petrol fumes as well as dust particles and residents living within 5 km of Mathura oil refinery. Control group comprised unexposed staff residing in the campus. PFT values were recorded and compared in the three groups. Results: Lowering of mean PFT values in residents and PPWs was observed. Forced vital capacity (FVC) (L), forced expiratory volume in 1 s (FEV1) (L), FEV1/FVC, and peak expiratory flow rate (L/s) were, respectively, 3.37, 2.93, 87.25, and 8.44 in control group (C); 3.09, 2.61, 85.2, and 7.94 in PPW and 3.0, 2.58, 86.0, and 7.94 in residents (R). Maximum ventilatory volume and forced expiratory flow rate 25–75% were also reduced in the latter groups. Conclusion: Acute exposure to a polluted environment results in an alteration of pulmonary functions.